Uptake of individual fatty acids into adipose tissue in relation to their presence in the diet. - Summers, L; Barnes, S; Fielding, B; Beysen, C; Ilic, V; Humphreys, S; Frayn, K (2000)
BACKGROUND: The fatty acid composition of adipose tissue triacylglycerol reflects, but is not identical to, the fatty acid composition of the habitual diet. OBJECTIVE: We investigated whether the fatty acid composition of adipose tissue is explained by differences between fatty acids in early storage in adipose tissue after a meal. DESIGN: Nine healthy men ate a meal containing several fatty acids. Blood samples were taken for 6 h after the meal from an arterialized hand vein and a vein draining the anterior abdominal subcutaneous adipose tissue. RESULTS: Net storage of fatty acids in adipose tissue occurred between 1 and 4 h after the meal. In relation to the amount fed, storage of fatty acids differed (P < 0. 01) between classes (n-3 polyunsaturated < saturated < n-6 polyunsaturated < monounsaturated); oleic acid was stored in the greatest amounts. These differences agreed closely with published data, except for n-3 polyunsaturated fatty acids. The only individual metabolic step at which significant differences between fatty acids was shown was incorporation of fatty acids into chylomicron triacylglycerol. Differences between fatty acids in rate of extraction from chylomicron triacylglycerol and net uptake into adipose tissue in the postprandial period were significant (P < 0. 01), but not when expressed in relation to proportions in chylomicron triacylglycerol. CONCLUSIONS: The characteristic fatty acid pattern of adipose tissue may predominantly reflect the early metabolic handling of different fatty acids. Adipose tissue uptake of n-3 polyunsaturated fatty acids is slow in relation to that of other fatty acids.